2012
DOI: 10.1093/abbs/gmr121
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholinesterase is associated with apoptosis in β cells and contributes to insulin-dependent diabetes mellitus pathogenesis

Abstract: Acetylcholinesterase (AChE) expression is pivotal during apoptosis. Indeed, AChE inhibitors partially protect cells from apoptosis. Insulin-dependent diabetes mellitus (IDDM) is characterized in part by pancreatic b-cell apoptosis. Here, we investigated the role of AChE in the development of IDDM and analyzed protective effects of AChE inhibitors. Multiple low-dose streptozotocin (MLD-STZ) administration resulted in IDDM in a mouse model. Western blot analysis, cytochemical staining, and immunofluorescence sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 33 publications
2
27
0
Order By: Relevance
“…Similar to fasted mice, FOR was able to rescue the low serum INS levels (Figure M) and induced an approximately 2‐fold increase in the muscle phosphorylation levels of Akt, FoxO1, ERK1/2, and CREB (Figure H–L) at 30 min in 3‐day STZ mice. Because it has been described that STZ reduces but does not eliminate INS from mouse pancreas, it is likely that the rise in INS levels caused by β 2 ‐AR stimulation in STZ‐treated mice comes from the remaining β‐pancreatic cells. To further evaluate the role of INS in the anti‐catabolic effects of FOR, muscle‐specific INS receptor (IR) knockout mice (M‐IR −/− ), which exhibit a muscle‐specific ablation of IR signalling, were fasted and then treated with FOR or saline.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to fasted mice, FOR was able to rescue the low serum INS levels (Figure M) and induced an approximately 2‐fold increase in the muscle phosphorylation levels of Akt, FoxO1, ERK1/2, and CREB (Figure H–L) at 30 min in 3‐day STZ mice. Because it has been described that STZ reduces but does not eliminate INS from mouse pancreas, it is likely that the rise in INS levels caused by β 2 ‐AR stimulation in STZ‐treated mice comes from the remaining β‐pancreatic cells. To further evaluate the role of INS in the anti‐catabolic effects of FOR, muscle‐specific INS receptor (IR) knockout mice (M‐IR −/− ), which exhibit a muscle‐specific ablation of IR signalling, were fasted and then treated with FOR or saline.…”
Section: Resultsmentioning
confidence: 99%
“…[39] Flowers are also found to contain lycopene and beta-carotene. Coumarins are also active constituents in CO.[40] These constituents may contribute to the antioxidant potential of this extract. The administration of acetylcholinesterase (AChE) inhibitors effectively decreased hyperglycemia and incidence of diabetes, and restored plasma insulin levels and plasma creatinine clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Induction and accumulation of AChE in pancreatic islets and the protective effects of AChE inhibitors on the onset and development of type 1 diabetes indicate a close relationship between AChE and type 1 diabetes. [40] AChE inhibitors enhance cholinergic function in the brain when loss or decline in memory and cognitive impairment has occurred. [4142] Polyphenols have shown AChE inhibitory effect[43] and considering that CO contains flavonoids,[36] another possible mechanism of CO effect on PAL can be involved in AChE inhibitory potential of the plant.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the present study showed that AChE activity in zebrafish was enhanced when exposed to combined stress of Cd and CBZ. The increase of AChE activity has been related to the production of free radicals [48] and to the apoptotic processes occurring in the organism [49,50]. AChE activity increase leads to fast acetylcholine degradation and downregulation of acetylcholine receptors, influencing the cognitive functions of the organism [51].…”
Section: Discussionmentioning
confidence: 99%